Image-Based Digital Face Identification Technologies: Criminal Law Aspect - Lykhova, Sofiia Ya.; Svintsytskyi, Andrii V.; Padalka, Andrii M.; Nizovtsev, Yuriy Yu.; Lyseiuk, Andrii (Law, State and Telecommunications Review, 2023)
[Purpose] The purpose of this article is to analyze the theoretical and practical aspects of digital face identification technology in Ukraine and suggest the necessary corrections to the optimal legal regime for the use of such technology in criminal proceedings. [Methodology/Approach/Design] The leading research method is the inductive method of the legal analysis that involves the problem formulation, analysis of the legal provisions regulating this question, practical study of the law enforcement, and formulation of conclusions. [Findings] In this article, the authors present a complex analysis of the Ukrainian legislation, define the particularity of criminal responsibility for the violation of privacy under the Ukrainian law in the context of the use of digital face identification technology, and suggest a list of reasonable amendments to the legislation to improve the level of such protection. [Practical Implications] The materials of this article have practical value for investigating crimes and protecting individuals against illegal use of their images by using digital face identification technology in the context of Ukrainian law. [Originality/Value] The topicality of the study is due to the fact that over the past decade face recognition has become one of the most powerful biometric technologies capable of identifying and verifying people involved in crimes based on digital images or video frames, but the legal regime of said identification had not yet been sufficiently explored in Ukraine.